Respuesta :
Answer:
x = negative 1 plus-or-minus StartRoot 17 EndRoot
Step-by-step explanation:
Given:
[tex]x^2+2x+1=17[/tex]
We need to solve for x.
[tex]x^2+2x+1=17 \ \ \ \ equation\ 1[/tex]
First we will solve L.H.S
Factorizing the equation we get;
[tex]x^2+2x+1\\=x^2+x+x+1\\=x(x+1)+1(x+1)\\=(x+1)(x+1)\\=(x+1)^2[/tex]
Now Things which are equal to the same thing are also equal to one another. Since
[tex]x^2+2x+1=17[/tex]
[tex]x^2+2x+1=(x+1)^2[/tex]
then, according to the law of transitivity,
[tex](x+1)^2=17[/tex]
Now, applying the Square Root Principle we get:
[tex]\sqrt{(x+1)^2} =\sqrt{17}[/tex]
Now Square root and square gets cancelled.
[tex]x+1=\sqrt{17} \\x=-1+\sqrt{17}[/tex]
Since a square root has two values, one positive and the other negative.
[tex]x=-1\±\sqrt{17}[/tex]
Hence Final Answer is [tex]x=-1\±\sqrt{17}[/tex].
Answer:
x = negative 1 plus-or-minus StartRoot 17 EndRoot
Step-by-step explanation: